2011
DOI: 10.1021/am200748y
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polyurethane Fibers for Absorption of Volatile Organic Compounds from Air

Abstract: Electrospun polyurethane fibers for removal of volatile organic compounds (VOC) from air with rapid VOC absorption and desorption have been developed.Polyurethanes based on 4,4-methylenebis(phenylisocyanate) (MDI) and aliphatic isophorone diisocyanate as the hard segments and butanediol and tetramethylene glycol as the soft segments were electrospun from their solutions in N,N-dimethylformamide to form micron-sized fibers. Although activated carbon possessed a many-fold higher surface area than the polyurethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 64 publications
(116 reference statements)
2
75
0
Order By: Relevance
“…It has been reported that electrospun nanofibrous mats are quite effective for particulate separation [2,3], liquid filtration [1][2][3], waste vapor treatment [4,5] as well as desalination [6]. Electrospinning has advantage over conventional membrane production techniques, since variety of functional nanofibrous materials can be easily obtained in the form of nonwoven membranes which can be readily used as a filtering material [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that electrospun nanofibrous mats are quite effective for particulate separation [2,3], liquid filtration [1][2][3], waste vapor treatment [4,5] as well as desalination [6]. Electrospinning has advantage over conventional membrane production techniques, since variety of functional nanofibrous materials can be easily obtained in the form of nonwoven membranes which can be readily used as a filtering material [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Biologically, hybrid nanofiber scaffolds have provided a cell niche conducive to improved attachment, proliferation, and cell differentiation [190][191][192][193][194][195][196][197][198], as well as targeted drug delivery carriers [198][199][200][201][202][203][204][205][206]. Filtration using ONFs [207] equipped with activated carbon has revealed adsorption of volatile organic compounds (VOCs) present in the air [208][209][210], and Scholten et al reported that adsorption and desorption of VOC by electrospun nanofibrous membranes (ENMs) were faster than that of conventional activated carbon [208]. Such examples demonstrate the pervasive nature of ONF systems, which will continue to provide innovative enhancement of technologies we use every day.…”
Section: Organic Micro-and Nano-fiber Systemsmentioning
confidence: 99%
“…Active carbon is the commonly used material to reduce the VOCs degree in the surrounding due to its high surface area and porous structure (Bradley and Rand, 1995;Bradley et al, 2011;Majumdar et al, 2001;Vermisoglou et al, 2007). However, the carbon based absorbents/adsorbents are generally applied in the powder or granular form and this creates challenges during their use in terms of handling and reusability (Scholten et al, 2011). For this reason, there are approaches in the literature including the formation of flexible nano-scaled matrix which were obtained with the incorporation of electrospinning technique (Bai et al, 2013a(Bai et al, , 2013bKatepalli et al, 2011;Kim et al, 2013;Lee et al, 2010;Scholten et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, there are studies in the literature reporting that, the electrospun NF were experienced as membrane system for VOCs filtration purposes. For instance, Scholten et al firstly used the electrospun polyurethane fibers for the removal of VOCs (Scholten et al, 2011). In another related study, reduced graphene oxide (RGO)/carbon composite ultrafine fibers were developed by using electrospinning and applying consequent carbonization to evaluate their VOCs adsorption performance (Bai et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%